Exchange Rate and Oil Price Interactions in Transition Economies: Czech Republic, Hungary and Poland - Bayat, Tayfur; Nazlioglu, Saban; Kayhan, Selim (Panoeconomicus, 2015)
This study investigates causal dynamics between crude oil prices and exchange rates in Czech Republic, Poland and Hungary by employing monthly data from the beginning of flexible exchange regime in each country to December 2011. The study benefits from the recent advance in the time series econometric analysis and carries out linear causality, non-linear causality, volatility spillover and frequency domain causality tests. The frequency domain causality analysis results imply that oil price fluctuations affect real exchange rates in the long run in Poland and Czech Republic. On the other hand, frequency domain causality test results indicate that oil price fluctuations do not affect exchange rate in any period in Hungary despite its economy’s high imported energy dependency. Key words: Oil prices-exchange rates relationship, Transition countries, Frequency domain. JEL: C32, F31, F41, Q43.